Stilbene Based Organic Dye as Efficient Sensitizer for NLO and Dye-Sensitized Solar Cells: A First Principle Study. (2019) - Prakasam, M.; Anbarasan, P.M.
Abstract: In this study, we have designed five different Stilbene based dyes as efficient sensitizers for Nonlinear Optical Properties (NLO) and Dye-Sensitized Solar Cells (DSSCs). Density Functional Theory (DFT) and Time-Dependent DFT (TD-DFT) have used to investigate molecular properties, in order to influence and performance of the dye sensitizer in the DSSCs. The theoretical result indicates that the HOMO and LUMO energy levels of this dye can be ensured a positive effect on the process of photoelectron injection into semiconductor surface and dye regeneration by the electrolyte. The solar energy conversion efficiency, effective key parameters in influence with the Short-Circuit Current Density ( JSC ), Light Harvesting Efficiency ( LHE ) and Electron injection driving force (Δ Ginject ) were discussed. The Stilbene-based dyes can be used as a potential sensitizer for photoelectron injection into the semiconductor surface due to its best electronic structure and optical properties of the good photovoltaic parameters.